ESG Disclosure and Financial Performance: Does Financial Slack Matter? A DuPont Analysis Approach - Ramadhani, Varra Nur; Laily, Nujmatul; Firmansyah, Rizky; Larasati, Ika Putri (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2026)
This study aims to analyze the effect of ESG Disclosure on financial performance, with Financial Slack serving as a moderating variable. The study employs an explanatory quantitative approach using 240 firm-year observations from 60 non-financial companies listed in the IDX ESG Leaders index in Indonesia over the period 2021–2024. Data analysis is conducted using panel data regression with a Moderated Regression Analysis (MRA) approach, processed through EViews software. The results indicate that ESG Disclosure does not have a significant effect on corporate financial performance, either when measured by Return on Equity (ROE) or by individual components of the DuPont analysis, namely Net Profit Margin (NPM), Total Asset Turnover (TAT), and Equity Multiplier (EM). Furthermore, Financial Slack is found to strengthen the positive effect of ESG Disclosure on Net Profit Margin (NPM). Overall, these findings reinforce the Resource-Based View (RBV) perspective, which posits that ESG Disclosure as an intangible resource requires the support of adequate Financial Slack as a tangible resource to create complementary capabilities and achieve sustainable competitive advantage. The findings provide practical insights for management to improve the quality of ESG disclosure and maintain sufficient levels of Financial Slack so that sustainability investments can generate long-term financial value. In addition, the results suggest that sustainability commitment supported by financial flexibility serves as an important signal for investors and regulators in assessing corporate performance and competitiveness